If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(X + 3) + -2 = 3 Reorder the terms: 5(3 + X) + -2 = 3 (3 * 5 + X * 5) + -2 = 3 (15 + 5X) + -2 = 3 Reorder the terms: 15 + -2 + 5X = 3 Combine like terms: 15 + -2 = 13 13 + 5X = 3 Solving 13 + 5X = 3 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5X = 3 + -13 Combine like terms: 13 + -13 = 0 0 + 5X = 3 + -13 5X = 3 + -13 Combine like terms: 3 + -13 = -10 5X = -10 Divide each side by '5'. X = -2 Simplifying X = -2
| 4=2(x-3)-2 | | 3.5x=-4.9 | | 45x+40x=55 | | x-2y+4x=10 | | s/3+4=6 | | x^2+y^2+2x-y+1=0 | | 153=x-11 | | 19-2+21=X-2 | | -9 = w5 | | c+-5=4 | | 9m-8m+20=87 | | -3=s-4 | | F(x)=4x^3-36x | | -13+5=X+9 | | -.07x+7.56=-0.3x+5.56 | | -3 = s-4 | | 19=4j-1 | | x+3.7=10.8 | | q+-25=3 | | 4(7-3x)+2x=108 | | 16=4f | | X-21=-36 | | x^2+2xyi-y^2=i | | 2+8(7-x)=82 | | (9x-2)+(x^2y+7)+6x+(x^2-9)=0 | | 3y+1=-10 | | Ax+bn=c | | 4.603y-1.842=-3.641 | | 0.9x-0.6(18-5x)=-0.3(X-6) | | y=3x^3-75x | | 8/3b+7/5= | | 15=.5a+13 |